Gestión administrativa del GAD Municipal del Cantón Ventanas, periodo 2023. - Intriago Intriago, Madeline Michelle (2024)
Administrative management in public companies is important for the timely development of the tasks performed, as well as the proper management of resources. It is the conjunction of the steps applied by managers, these are planning, organization, direction and control within the same, they provide experience to a company and it is used throughout the world because it allows the development and use of resources and money. In this sense, it allows tasks to be carried out in an orderly manner and accurate decisions to be made. The present case study focused on carrying out an analysis of the administrative management of the Decentralized Autonomous Government of the Ventanas canton during the period 2023. It is a public institution dedicated to providing service to the community through the efficient administration of the available assets of the canton, the methodological approach research method was used where research techniques were used through the application of a survey to the staff, and to the users of the institution, likewise, an evaluation matrix of the internal factors was carried out allowing the collection of relevant information where it was obtained that the municipality presents difficulties in the development of its functions due to poor planning and manual of processes that lead to the timely development of its actions to be efficient, therefore the response time of requests from citizens is high, which is why they feel dissatisfaction with the inefficient service offered by the municipality, in addition to not constantly training employees that allow them to expand their knowledge, develop skills to provide quality services to citizens.